Electricity generation from phase-engineered flexible MoS2 nanosheets under moisture. (March 2021) - He, Dunren; Yang, Yaocheng; Zhou, Yuan; Wan, Juanyong; Wang, Heao; Fan, Xi; Li, Qi; Huang, Huihui
Abstract: Hydroelectricity is an emerging novel electricity generation phenomenon that the hydrogen bond energy is converted into chemical potential energy as electric power source by absorbing moisture. Here we report a high-performance water vapour energy harvester based on flexible MoS2 nanosheets with a phase gradient from 1T to 2H. The phase-engineered MoS2 film could provide open-circuit voltage and short-circuit current output of 19 mV and 6.24 µA with a low internal resistance of 3 kΩ. Additionally, the underlying mechanism of electricity generation from phase-engineered MoS2 films was proposed in terms of contrast experiments and the plane wave density functional theory (DFT). Because of the advantages like flexible, safe, light weight and ease of scale production, this novel hydrovoltaic device could be designed as self-powered human-breathing monitor that can be integrated in disposable masks. The output voltage can be further enhanced to power commercial electronic devices by the serial connections of phase-engineered MoS2 sponges. Graphical Abstract: ga1 Highlights: A moisture-induced electricity generator based on the phase-engineered MoS2 film is produced. The phase-engineered MoS2 film could provide an electric output of 19 mV and 6.24 µA with a low internal resistance of 3 kΩ. The underlying mechanism has been explored by contrast experiments and first-principle calculations. The output voltage can be further enhanced to power liquid crystal displays clock and light emitting diodes.